Comparative Performance of Puddlers in Low Lands of Hilly Areas - Kumar, Arvind; Mandal, S.; Singh, R. K.; Tamhankar, M. B. (Indian Journal of Hill Farming, 2015)
A comparative study of the quality of puddled soil and energy requirement was carried out with animal drawn traditional country plough (T1), rectangular blade puddler (T2), disc harrow (T3) and power tiller operated rotavator (T4). Weeding efficiency, puddling depth, percentage increase in bulk density, puddling index, percolation rate and energy requirement were studied for the above treatments. Puddling performance by different implements in comparison to the traditional animal drawn country plough (T1) shows that there is a definite reduction in time requirement for field preparation. Increase in weeding efficiency, bulk density and puddling index were also observed. The highest values of weeding efficiency and puddling index were found 69.3% and 51.5, respectively, for power tiller rotavator (T4). The total time requirement for preparation of puddled field for treatment T4 was found to be the lowest (27.4 h/ha). Energy requirement for preparation of puddled field was found highest (2844.91MJ/ha) for power tiller operated rotavator (T4) followed by T1, T3 and T2 treatments.